Near-complete genome sequence of an enterovirus species F isolate recovered from sewage in Nigeria (2020)
Here, we describe the near-complete genome of an enterovirus F (EV-F) isolate from Nigeria. The obtained sequence was 7,378 nucleotides (nt) long and encodes 2 open reading frames (ORFs), an upstream ORF (uORF; 56 amino acids [aa]) and a polyprotein ORF (ppORF; 2,167 aa). Both ORFs overlap but are in different reading frames, with the uORF in a +1 reading frame relative to the ppORF.